Green synthesis of silver nanoparticles using Eugenia uniflora extract, its characterization, antioxidant, and anti‑inflammatory activities - Oriola, Ayodeji O.; Kar, Pallab; Oyedeji, Adebola O. (Journal of Phytology, 2025)
Nowadays, the use of environmentally benign raw materials, especially medicinal plants, is preferred in the preparation of nano substances known as nanoparticles (NPs), for use in various biological applications. Eugenia uniflora is an edible plant with enormous medicinal uses owing to its rich phytochemical content. Therefore, this study was carried out to obtain an E. uniflora extract-based silver nanoparticles (Eu-Ag NPs), and to elucidate its antioxidant and anti-inflammatory potential. The NPs were prepared by a conventional green synthesis method. The ultraviolet visible (UV-Vis) and energy-dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD) method, and field emission scanning electron microscopy (FESEM), assisted with characterization of the NPs. In vitro antioxidant analysis was based on hydrogen peroxide (H2O2), nitric oxide (NO), superoxide, and hydroxyl radical scavenging assay methods. The inhibitory effect of the NPs on egg albumin denaturation (EAD) was used for the in vitro anti-inflammatory screening. Morphological assessment of the Eu-Ag NPs by FESEM revealed the shape to be spherical to cubical. The maximum absorption peak at 410 nm suggests the formation of AgNPs, while the conversion of metallic silver into elemental silver was confirmed by EDX with 99.50%. The FESEM showed a median size of 45.35 nm for the NPs. The Eu-Ag NPs had good antioxidant and anti-inflammatory potentials, exhibiting an IC50 of 48.91±0.12 and 157.41±0.90 μg/mL against H2O2 radical and EAD, respectively. This study has shown that E. uniflora leaf aqueous extract-mediated silver nanoparticles possess unique structural attributes with considerable antioxidant and anti-inflammatory properties.